2018
DOI: 10.1007/s00784-018-2488-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical sensitivity and psychological factors in patients with burning mouth syndrome

Abstract: Pain on the tongue in elderly female patients with BMS may be more related to psychological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
0
32
1
2
Order By: Relevance
“…Anxiety and depression play critical roles in BMS according to the latest systematic review and meta‐analysis published by Galli et al (2017) and some studies subsequent to this paper (Adamo et al, 2019; Honda et al, 2019; Yoo et al, 2018). There are previous studies like Schiavone et al (2012); Lee, Kim, and Kim (2019) and Yoo et al (2018) that used SCL‐90‐R questionnaire.…”
Section: Discussionmentioning
confidence: 78%
“…Anxiety and depression play critical roles in BMS according to the latest systematic review and meta‐analysis published by Galli et al (2017) and some studies subsequent to this paper (Adamo et al, 2019; Honda et al, 2019; Yoo et al, 2018). There are previous studies like Schiavone et al (2012); Lee, Kim, and Kim (2019) and Yoo et al (2018) that used SCL‐90‐R questionnaire.…”
Section: Discussionmentioning
confidence: 78%
“…The search identified a total of 123 records from the six databases. Therefore, 13 articles and one conference abstract were included in the study, but the proportion of articles reporting specific outcomes was calculated based only on the 13 full articles [32][33][34][35][36][37][38][39][40][41][42][43][44] (Figure 1).…”
Section: Re Sultsmentioning
confidence: 99%
“…3,23, Due to the high variability of the protocols, equipment and outcomes of the studies, the results from five of the articles (38.5%) were only compared qualitatively (Table 1). 33,37,38,41,44 All the other studies (61.5%) were considered for meta-analysis. 31,[33][34][35]38,39,41,42 However, WDT, CDT, HPT, CPT and MPT were the only comparable outcome measures reported by more than one article.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that sleep disorders have the potential to increase the risk of BMS . To clarify the mechanism of BMS, our previous study investigated the effects on tongue sensitivity to the topical application of capsaicin (as a surrogate model of BMS) using a standardised battery of quantitative sensory tests (QST) . In addition, we investigated reports of perceptual distortion evoked by transient deafferentation and burning pain as models of some aspects of BMS, and the results suggested that perceptual distortions of the tongue may be influenced by non‐nociceptive somatosensory changes rather than nociceptive activity .…”
Section: Introductionmentioning
confidence: 99%